2021
DOI: 10.12659/msm.932032
|View full text |Cite
|
Sign up to set email alerts
|

Ratio of Serum Calcium to Magnesium Levels on Pregnancy With and Without Preeclampsia

Abstract: Background Preeclampsia increases maternal and perinatal mortality and is affected by calcium and magnesium levels. Reduced extracellular levels of calcium and magnesium constitute the pathogenesis of eclampsia. A reduction in the calcium-magnesium ratio may aid in the detection and prevention of preeclampsia. Material/Methods This was an analytical observational study with a cross-sectional design, including patients with and without preeclampsia (inpatient and outpati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Accumulating evidence shows that there is an increased magnesium intake requirement during pregnancy due to the need for fetus bone formation ( Fanni et al, 2021 ). Moreover, Winarno et al showed that patients with preeclampsia had significantly lower serum calcium-magnesium ratios than did healthy pregnant women; therefore, magnesium deficiency status during gestation may interfere with fetal growth and development and may lead to premature labor ( Winarno et al, 2021 ). Other clinical trials have associated intrauterine growth restriction (IUGR) with a higher risk of undergoing insulin resistance later in life, suggesting that chronic intrauterine magnesium deficiency might result in IUGR.…”
Section: Resultsmentioning
confidence: 99%
“…Accumulating evidence shows that there is an increased magnesium intake requirement during pregnancy due to the need for fetus bone formation ( Fanni et al, 2021 ). Moreover, Winarno et al showed that patients with preeclampsia had significantly lower serum calcium-magnesium ratios than did healthy pregnant women; therefore, magnesium deficiency status during gestation may interfere with fetal growth and development and may lead to premature labor ( Winarno et al, 2021 ). Other clinical trials have associated intrauterine growth restriction (IUGR) with a higher risk of undergoing insulin resistance later in life, suggesting that chronic intrauterine magnesium deficiency might result in IUGR.…”
Section: Resultsmentioning
confidence: 99%
“…This ratio is also greater than that of 18–44-year-old Chinese childbearing women (2.41–3.44) [ 14 ]. Gatot Winarno’s research [ 29 ] used a receiver operating characteristic curve (ROC) analysis on the serum Ca/Mg ratio and showed that women with a serum Ca/Mg ratio of <2.36 were predicted to have a risk of preeclampsia. Qing Li [ 30 ] used the data of a prospective cohort study of 3380 coronary artery disease (CAD) patients to assess the associations of plasma Ca/Mg ratio with mortality in patients with CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Other experimental data suggest that a higher intracellular Ca/Mg ratio, induced by a diet elevated in Ca and deficient in Mg, may cause HTN, IR, and MetS [ 161 ]. Women with preeclampsia had a meaningfully higher mean serum Ca/Mg ratio than women without preeclampsia [ 162 ]. Moreover, the Ca/Mg ratio plays the main role in the stimulation and transmission of nerve cell signals.…”
Section: Discussionmentioning
confidence: 99%